Flexible cooperative game theory tool for peer-to-peer energy trading analysis - Dixon, J; Morstyn, T; Han, L; McCulloch, M (IEEE, 2018)
This paper presents an extensible and adaptable tool with which to study the use of cooperative game theory for allocating rewards to prosumers in peer-to-peer (P2P) energy trading systems. With the aim of expanding the use of renewable generation, the tool is a combination of the cooperative game theory platform and a specific game which focuses on a prosumer P2P network in a distribution network feeder. The final platform is able to run user defined P2P trading games, including the aforementioned one, over multiple trading intervals. It has two inbuilt allocation schemes which can be tested on the games for fairness and stability.